Financial Insights and Risk Attitudes: Driving Firm Performance in Malang's Food and Beverage SMEs - Fitria; Wati, Cicik Retno; Fadhila, Wildan (Jurnal Manajemen Agribisnis dan Agroindustri, 2024)
This study aims to analyze and understand the relationship between financial knowledge, financial behavior, and firm performance. The study was conducted on 120 food and beverage SMEs in Malang. The sampling technique used was purposive sampling with several criteria. The sample size was determined by multiplying 12 research indicators by 10, following the approach of JR. et al. (2022). The data analysis in this study used SEM-PLS, assisted by the SmartPLS 3.3.3 software. The results indicate that financial behavior and financial risk attitude significantly affect firm performance, while the relationship between financial knowledge and firm performance yielded different results. The testing shows that financial knowledge does not significantly affect firm performance. Furthermore, these findings suggest that the level of financial knowledge among SME actors in Malang does not sufficiently support the improvement of SME firm performance. The low level of financial knowledge also leads SME actors to be more cautious in making financial and business decisions, as they can better assess the extent of business and financial risks they may face. Therefore, further training is needed to enhance the financial knowledge and capabilities of SME actors, particularly in the field of finance.